Publication performance without calculations: an analysis based on the p-index - Simões, N.; Crespo, N. (Current Science, 2019)
In universities and other research institutions, critical decisions (e.g., hiring, promotions, awards, and research funds allocation) are supported by bibliometric measures. The present study contributes to the literature by proposing a measure of publication performance. Our index (p'-index) takes the p-index suggested by Prathap (2010a,b) as starting point. With a small adjustment in the p-index, we obtain a measure that does not require any form of calculations. We build a table (presented in this study as online appendix) showing the final performance scores for each combination of: (i) total number of papers and (ii) total number of citations. The evidence shows that this new metric is almost perfectly correlated with the p-index (0.999), meaning that we can reach the same conclusions without having to make calculations.